MOTIVATION-IN-CONTEXT: A STUDY OF L2 IDENTITY FORMATION IN A DOMINANTLY L1 UNIVERSITY ENVIRONMENT - Shanmuganathan, Sharmi (Sanata Dharma University, Yogyakarta, 2025)
This study was conducted to identify the interplay between the formation of self-image and the perception of learners about their identity as Sri Lankan English speakers. Motivation in language learning has been associated with various factors (motives) that play a role in persuading the learners to learn a language. Recent research in motivation have picturised motivation as a crucial element in language learning which is affected by a host of other factors that are contextually unique. In Sri Lankan tertiary learning environment, the need for English language has been felt mostly in the higher education and employment of the graduates. Thus, I aimed at obtaining answer to the question whether and how the learning experiences learners gain in the university of Jaffna motivate them to accomplish their language goals. I wanted to examine the role of their perception of their identity English speakers since this realisation is significant in pushing a learner forward to achieve their language goals. I used mixed methods research and gathered data from forty participants using questionnaire and selected five among them for semi-structured interview. Results revealed that compared to their school learning experiences, university provided them with adequate opportunities to be in English speaking environment and factors like their self-confidence, social expectations, and socioeconomic background supported in this process. However, since most of these opportunities were provided outside their language classroom, they benefitted only a few learners. Therefore, it is recommended that language classrooms provide more such opportunities relevant to learners' proficiency.